BALANCE AND SPEED CONTROL SETTING ON SEGWAY UTILIZING PID CONTROL - Fatanur Baity Tsulutsya; Miftahul Choiro; Hairil Budiarto; Ach Kusairi (Universitas Trunojoyo Madura, 2023)
Segway is an innovation that utilizes an inverted pendulum model placed on top of a wheeled platform to create a transportation device capable of balancing itself. This research aims to investigate the balance and speed control settings on the Segway. The objectives are to address the balance issues of the Segway and determine the working system used. The study involves the analysis of components, circuitry, and mechanical design to overcome existing challenges. A BLDC (Brushless Direct Current) motor is employed to maintain the Segway's stability while in an upright position. An MPU-6050 sensor functions as a readout for the Segway's angle and position under various conditions. The control system used is Proportional Integral Derivative (PID). The PID method is applied using angle data from the MPU-6050 sensor to maintain balance on the Segway. This helps reduce errors and makes the Segway's movements smoother and more stable. In this research, the Segway can move after self-balancing with a maximum tilt angle of 30º. The PID values used are Kp = 48, Ki = 3.5, and Kd = 1.6.